ATHEROSCLEROSIS PREDICTION SYSTEM BASED ON THE IDENTIFICATION OF THE MOST SIGNIFICANT RISK FACTORS IN WORKERS OF THE MAIN PROFESSIONS OF THE COAL INDUSTRY IN THE SOUTH OF KUZBASS - Филимонов, Егор Сергеевич; Коротенко, Ольга Юрьевна (Medicine in Kuzbass, 2022)
Subject of the research. 266 workers of coal mines in the South of Kuzbass (sinkers, stope miners, operators of mining machines) working in harmful working conditions and not having occupational diseases were examined. All the examined men were from 40 to 54 years old, the average age was 46.4 ± 0.38. Objective of the research was to elaborate a system for predicting cardiovascular diseases based on the identification of the most significant risk factors in workers of the main professions of the coal industry in the South of Kuzbass. Methods of the research. All patients underwent an ultrasound investigation of the brachiocephalic arteries and arteries of the lower extremities, an assessment of the external respiration function, the calculation of the Quetelet index and the waist/hip ratio, the smoker’s index; lipid profile, glycemia and glycated hemoglobin in blood serum were studied. The presence of arterial hypertension and a burdened family history of cardiovascular diseases was clarified. Main results. Based on work experience in harmful working conditions, impaired external respiratory function, smoking, burdened family history, obesity, increased ratio of waist circumference to hip circumference, fasting hyperglycemia, increased glycated hemoglobin, hypercholesterolemia, increased low-density lipoprotein cholesterol, triglycerides and atherogenicity coefficient, as well as a decrease in high-density lipoprotein cholesterol prognostic coefficients were calculated, by the sum of which it was possible to determine the probability of developing arterial hypertension and atherosclerosis in coal industry workers. Conclusions. Determination of risk factors for atherosclerosis development in workers of the main professions of the coal industry makes it possible to predict its development, which will allow timely implementation of therapeutic and preventive measures.